Yesterday's tomorrow is not today. Memory and place in an Algiers neighbourhood - McAllister, E (2015)
Since the euphoria of a hard-won independence and the hopes attached to socialist nation-building, Algeria has experienced liberalisation, increasing inequality and civil war. This thesis sets out to explore memories of post-independence nation-building in the 1970s, interrogating the past-present relationship, by asking how Algerians remember their own recent past, and what these memories reveal about contemporary subjectivities. Based on a year of ethnographic fieldwork in the low-income Algiers neighbourhood of Bab el-Oued, the research focuses specifically on memories of politics, urban space and sociability. While the authoritarianism of the period was rejected for its repression of civil liberties, the overwhelming narrative on the period was nostalgic, with the past routinely couched as more positive than the present. Memories of intense social mobility and rising living standards within the context of state-led development, competent urban management and warm neighbourhood relations governed by traditional morality and solidarity were used to critique the present; particularly the retreat of the state from its responsibilities since the 1980s and the fragmented, consumerist society that has emerged from civil conflict since the 1990s. However, social memory also translated a series of principles that demonstrated the continued relevance of the egalitarian claims made by postcolonial nationalism. Popular notions of social justice mapped future aspirations for the Algerian polity. Nostalgia was not only a matter of the past, but of the lost future of material plenty and equality promised by industrial modernisation that once seemed just over the horizon, but is now divorced from present experience. Such memories translated the passing of the dream of mass utopia, even though the modernist principles of equality, justice and progress continued to underpin both daily interactions and the political aspirations of the present.